FUZULİ VE ŞEYH GALİB DİVANLARINDA NEY METAFORU - ÖZTEKİN, MAHMUT BOLKAR (Fırat Üniveristesi, 2007)
Şeyh Gâlîb ve Fuzûlî Dîvânlarında Ney Metaforu? başlıklı çalışmamız, Mevlânâ'nın Mesnevî'si ile çok bilinen `ney' sembolünü Fuzûlî ve Şeyh Gâlîb Dîvânlarında inceleyip, göstermeyi amaçlamaktadır. Bu amacımızın, hem Türk Mûsikîsi hem de Türk Edebiyatı alanı okuyucuları tarafından iyice anlaşılabilmesi için giriş bölümünde; `Ney'in Etimolojisi ve Tarihçesi, Yapısı ve Özellikleri, Türk Edebiyatı'nda Mûsikî ve Ney, Mevlânâ ve Mûsikî, Mesnevî'deki İlk Onsekiz Beyitin Açıklaması vb., birinci ve ikinci bölümlerde Fuzûlî ve Şeyh Gâlîb Divanlarında Ney Metaforu incelenmiş ve Ney ile ilgili olan bütün beyitler tespit edilerek açıklanmıştır

The study named ?The Ney Metafor in the Şeyh Galib?s and Fuzuli?s Literature? aims to show the denote ney symbol which is well known by Mesnevi of Mevlana Jalaladdin Rumi in the Şeyh Galib?s and Fuzuli?s divan. In order to make our target understood better by the readers of Turkish Literature fields, the introduction part includes etymology and short history of ney, Mevlana and music, explanation of the first eighteen couplets in the Mesnevi etc. In the first and second sections, ney metafor has been examined in the Şeyh Galib?s and Fuzuli?s divan and all of the couplets relation with ney have been fixed and explained
The ney metafor in the Şeyh Galib's and Fuzuli's literatures
Keywords: Türk Dili ve Edebiyatı